#1**+1 **

Simplifying -6(v + 1) + 8 = 2(v + -3)

Reorder the terms: -6(1 + v) + 8 = 2(v + -3) (1 * -6 + v * -6) + 8 = 2(v + -3) (-6 + -6v) + 8 = 2(v + -3)

Reorder the terms: -6 + 8 + -6v = 2(v + -3)

Combine like terms: -6 + 8 = 2 2 + -6v = 2(v + -3)

Reorder the terms: 2 + -6v = 2(-3 + v) 2 + -6v = (-3 * 2 + v * 2) 2 + -6v = (-6 + 2v)

Solving 2 + -6v = -6 + 2v Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '-2v' to each side of the equation. 2 + -6v + -2v = -6 + 2v + -2v

Combine like terms: -6v + -2v = -8v 2 + -8v = -6 + 2v + -2v

Combine like terms: 2v + -2v = 0 2 + -8v = -6 + 0 2 + -8v = -6

Add '-2' to each side of the equation. 2 + -2 + -8v = -6 + -2

Combine like terms: 2 + -2 = 0 0 + -8v = -6 + -2 -8v = -6 + -2

Combine like terms: -6 + -2 = -8 -8v = -8

Divide each side by '-8'. v = 1

Simplifying v = 1

cheifraidhunter
Jun 8, 2017